Peningkatan Kinerja Karyawan Melalui Motivasi Dan Keterampilan Kerja Pada CV. Catur Bhakti Mandiri - Martini Martini; Fiderius Ismanto (Anindyaguna Ekonobisnis : Jurnal Ekonomi dan Bisnis STIE Anindyaguna, 2021)
Human resources are the main driving force for the running of an organization'sactivities, the back and forth of an organization is determined by the existence ofits human resources. This study aims to examine and analyze the factors thatinfluence employee performance through work motivation and work skills at CV.Catur Bhakti Mandiri, in this study using a 1-10 scale questionnaire with 35respondents and using a sampling technique using saturated sampling or census.The data obtained were then analyzed with the SPSS program.The results of this study prove that to improve employee performance canbe increased through continuous motivation and seeing the skills possessed by eachemployee, because there is a tendency for employees to prefer to work if it is inaccordance with the skills they have and of course this has a big impact onperformance. them in a company.Keywords: Employee Performance, Skills, Work Motivation